A Decision Support System for smallholder campesino maize-cattle production systems of the Toluca Valley in Central Mexico. Part II—Emulating the farming system - Castelán-Ortega, O.A.; Fawcett, R.H.; Arriaga-Jordán, C.; Herrero, Mario (Elsevier, 2003)
This paper describes the functioning and validation of the Decision Support Systems described in the first part of the paper. The DSS ran three case studies with different farm sizes that represent the range of farmers found in the Valley. The DSS results were validated against survey data for the same cases. Traditional technologies for maize and milk production were reproduced by the DSS including land use and cattle feeding systems. The generic nature of the DSS was demonstrated as well as its capacity to deal with the system's socio-economic and biological aspects. The results suggest that the DSS was successful in reproducing the functioning of the farming system's main components. More importantly it simulated the complex interactions observed between the farmers and their crops and cattle. Finally, it is acknowledged that despite the size and complexity of the DSS, it only was able to emulate the functioning of the main components of the farming system.